Upaya Penanggulangan Kebocoran Data Pribadi pada Aplikasi Lacak Pasien Corona Melalui Pemberlakuan UU PDP dan Pendayagunaan Anonymity/Pseudonymity - Syifa Addini Humairah (Jurnal Hukum Lex Generalis, 2023)
Covid-19 is legally included in the Pandemic category by the World Health Organization (WHO). Based on its type, this research is normative juridical research using secondary data sources and tertiary data as supporting data. Data analysis using Statute Approach and Conceptual Approach. This research found that since Indonesia became a member of APEC, the government has not shown seriousness in creating a Personal Data Protection Law independently. So it requires a study related to Personal Data Protection arrangements in Indonesia after the PDP Law. Regarding the PeduliLindungi (SatuSehat) application as a tangible manifestation of government steps, it is necessary to utilize the concept of anonymity/pseudonymity to overcome personal data leakage that occurs in the PDP Law.